The Impact of Aggregation of Quaterthiophenes on the Excited State Dynamics - Ghosh, Srijon; Jana, Bikash; Ghosh, Arnab; Guldi, Dirk Michael; Patra, Amitava (Journal of Physical Chemistry Letters, 2021)
Oligothiophenes and their aggregates play a dominant role in optoelectronic and light-harvesting applications. Here, we controlled the degree of aggregation of 2,2':5',2″:5'',2‴-quaterthiophene (QTH) to shed light on the impact of the aggregation on the excited state dynamics. QTH aggregation realized the control over the Intersystem Crossing (ISC) rates and, in turn, the formation of triplet excited states via the simple addition of water to QTH solutions in THF. From global target analysis, the time scale was 345.5 ps for ISC for QTHs in THF, but it was 2.33 ns in the case of QTH solutions featuring 70% water. Notably, the excitonic coupling between closely packed QTHs occurred predominantly in the aggregates formed in the presence of large water concentrations. Relaxation dynamics of the resulting QTH-aggregates differed substantially from QTH solutions at lower water content. For example, QTH-aggregates lacked any triplet excited states, and the unusual emission occurs from lower excitonic states from these predominantly H-aggregates.
CRIS-Team Scopus Importer:2021-04-19